The influence of religious/spiritual beliefs on Malaysian hospital healthcare workers' attitudes towards suicide and suicidal patients: a qualitative study. (December 2021) - Siau, Ching Sin; Wee, Lei-Hum; Wahab, Suzaily; Visvalingam, Uma; Yeoh, Seen Heng; Halim, Nur Atikah Abdul; Ibrahim, Norhayati
Background: There has been mixed findings on whether a healthcare workers' religious beliefs contribute positively or negatively to their attitudes towards suicidal patients. Aims: This study aims to explore qualitatively the influence of religious/spiritual beliefs on healthcare workers' attitudes towards suicide and suicidal patients in the culturally heterogeneous Malaysian population. Methods: Thirty-one healthcare workers from diverse religious backgrounds, professions and medical disciplines were interviewed. Thematic analysis revealed the centrality of religion in determining healthcare workers' acceptability of suicide, specific religious beliefs that influenced their views on the right-to-die issue, perceptions of the suicidal patient's religiousness/spirituality, and the aspects and extent of religious relevance in professional philosophy and practice. Results: Healthcare workers who could perceive the multifactorial nature of suicide causation had a more empathetic response. There were high levels of paternalism in the care of suicidal patients, involving unsolicited religious/spiritual advice practised as a form of suicide deterrent and social support. Conclusions: The formal integration of religious/spiritual practices into the professional care of suicidal patients was indicated.